Bio-Inspired Sutures: Localizing Damage by Isolating Strain Energy - Diana A. Chen; Melissa M. Gibbons (Biomimetics)
This study draws upon bio-inspiration from anatomical sutures found in hard structures, such as turtle shells, to explore if impact energy can be dissipated through geometric parameterization rather than relying on energy-absorbing materials. While previous finite element analysis studies identified optimal dovetail suture geometries for maximizing the global stiffness and toughness of archway structures, this paper explores how different suture geometries might optimize localization effects through segmentation to isolate damage caused by the propagation of strain energy. We compare the global toughness of each suture geometry to its scaling factor, defined as the ratio of strain energy in the center segment(s) of the archway over the total strain energy absorbed during deformation, normalized by the expected strain energy consistent with uniform volumetric distribution. Our findings indicate that the scaling factor tended to correlate positively with global toughness, suggesting that suture geometries that performed well globally would also exhibit the localization effect. However, there is some nuance in selecting suture geometries that perform well for both metrics, as well as ensuring that geometries that perform well for one type of segmentation are still structurally sound in others, due to little control over where impact may occur, relative to the location of a suture, in real scenarios.